Hydroxypropylation for functional enhancement of sago starch: The effects of low propylene oxide concentration using response surface methodology - Derina Paramitasari; Musa Musa; Okta Nama Putra; Suparman Suparman; Yanuar Sigit Pramana; Sarah Elisa; Taufik Hidayat; Agus Eko Tjahjono; Dyah Primarini Meidiawati; Karjawan Pudjianto; Arni Supriyanti (Journal of Agriculture and Food Research, 2024)
Native sago starch is currently limited to food and adhesives due to its functional constraints, requiring improvement for broader industrial use. Hydroxypropylation is a modification technique used to enhance the functional properties of starches. However, propylene oxide usage is restricted owing to safety and environmental concerns during the modification process. Therefore, hydroxypropylation with a low dose of propylene oxide was selected to improve the functional characteristics of the sago starch with the desired molar substitution. The Response Surface Methodology (RSM) was chosen to optimize hydroxypropylation with the following factorial process variables: volume of 7 % w/w propylene oxide (6–18 ml), reaction pH (9−12), reaction time (3–8 h), and the desired molar substitution (MS) as a response variable was 0.100. The optimization was achieved at 17.03 ml of 7 % wt. of propylene oxide, reaction pH 11.92, and reaction time of 3 h. Hydroxypropylation has effectively increased the functional properties of sago starch including swelling power, water-holding capacity, oil-holding capacity, and solubility of sago starch as well as paste and setback viscosity. However, hydroxypropylation reduced the amylose content, gelatinization temperature, and breakdown viscosity. The RSM with a low propylene oxide concentration successfully optimized sago starch hydroxypropylation and enhanced its functional properties. Hydroxypropylated sago starch using low propylene oxide could be further studied as a potential thickener in the food industry.